Interações multimodais na clínica de linguagem: a criança com síndrome de down - Lima, Ivonaldo Leidson Barbosa (2016)
The Down syndrome (DS) is a disease resultant of the extra presence of a 21 chromosome, which can cause various health problems (for example: delay on global development, vision and hearing problems), as well as cognitive and language deficit. Studies claim that children with DS show a lexical repertory same as children with language development considered typical, but they show phonologycal, syntactic alterations and pragmatic skills. On the other hand, they show preference on the gesture medium [or its association with the words], which favors the language development and becomes their nonverbal communication an effective device of interaction. In this sense, this study objective is to analyze the constitutive process of the language pattern in the child with Down syndrome in a clinical context. For this, records of a speech-language therapy of therapists-child was taken on the Clinic-School of Speech, Language and Hearing Sciences in an Institution of Higher Education in Paraíba: the therapists were students of Speech, Language and Hearing Sciences, extension students of a project that promotes speech-language intervention to individuals with DS; the child is a boy with DS who was 18 months and 25 days old in the beginning of the collection. The collections were weekly, with duration of 30 minutes and occurred with the consent of the responsible for the children and the students that lead the intervention process. After that, we analyze the videos in the ELAN software to describe quantitative and qualitatively the language relations built between the subjects language. The Committee of Ethics in Research of the origin institution approved the research by the decree nº 1.360.357. It was found that the speech-language therapy favored the process of constitution of the child’s linguistic matrix with Down syndrome, which can be verified by expanding the amount of vocal and gestural productions in a few sessions examined [session 1 - n = 22 / session 6 - n = 72]. In addition, at the beginning of the therapeutic process, the child was more frequent use of gesture productions [session 1 - n = 14] than the vocal [session 1 - n = 8], but with the following the intervention there was a greater synchrony between the productions [gestures at the session 6 - n = 37 / speak at session 6 - n = 35]. Finally, we note that there is a joint growth of the linguistic matrix (p = 0.004) and gesture productions (p = 0.001) of the child and its insertion into joint attention scenes.